1999
DOI: 10.1128/cdli.6.3.440-443.1999
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Early Antibiotic Treatment on the Antibody Response to Cytoplasmic Proteins of Brucella melitensis in Mice

Abstract: To test whether antibiotic therapy hampers the antibody response toBrucella antigens, 30 BALB/c mice were infected withBrucella melitensis H38 and randomized for treatment with doxycycline administered intraperitoneally for 42 days starting at 7 or 28 days postinfection (p.i.) (groups DOX7 and DOX28, respectively) or for no treatment (control group). Antibodies to smooth lipopolysaccharide (LPS) reached peak levels (mean optical density [OD] = 2.618) between days 56 and 70 p.i. in the control group, and simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The most commonly used tests are the Serum Agglutination Test (SAT), the Coombs anti-Brucella test, the Rose Bengal Test (RBT) and complement fixation. During the last decade, radioimmunoassay [7,8] and enzyme immunoassay [9][10] tests have also been used. These present technical difficulties since they require skilled personnel and high-cost material.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used tests are the Serum Agglutination Test (SAT), the Coombs anti-Brucella test, the Rose Bengal Test (RBT) and complement fixation. During the last decade, radioimmunoassay [7,8] and enzyme immunoassay [9][10] tests have also been used. These present technical difficulties since they require skilled personnel and high-cost material.…”
Section: Introductionmentioning
confidence: 99%
“…The retention of the implant and degree of debridement used in this study may have allowed the establishment of a biofilm with subpopulations of bacteria that were unaffected by the specific antibiotic used, and which were able to proliferate with increased time from debridement and completion of antibiotic therapy. In addition, besides killing or inhibiting the growth of microorganisms, antibiotics may blunt the host immune response to infection, similar to the way it impairs antibody response to some infections [2,20,33]. For example, there is evidence that antibiotics may affect the metabolism of bacteria [12], and may interfere with phagocyte function [10,14] and cytokine production [l].…”
mentioning
confidence: 99%
“…They identified in mice that commencement of doxycycline at seven days post vaccination (for Brucella melitensis) resulted in complete reduction of IgG specific www.nature.com/scientificreports www.nature.com/scientificreports/ antibodies for greater than 50 days. Conversely, if antibiotics were commenced 28 days post vaccination, IgG specific antibodies were observed to remain, although at lower levels, compared to no antibiotic treatment 32 . In the current koala trial, all animals had pre-existing Chlamydia infections that had persisted long enough to cause signs of cystitis.…”
Section: Discussionmentioning
confidence: 88%
“…The lasting effect that antibiotics have on the humoral immune response has been demonstrated to depend on the antibiotic used, the dose schedule and the antigen used to vaccinate 30 . Bowden et al (1998) identified that the time between vaccination and commencement of antibiotics can significantly affect the development of antigen specific IgG antibodies 32 . They identified in mice that commencement of doxycycline at seven days post vaccination (for Brucella melitensis) resulted in complete reduction of IgG specific www.nature.com/scientificreports www.nature.com/scientificreports/ antibodies for greater than 50 days.…”
Section: Discussionmentioning
confidence: 99%